Are The Banks on The Way of Sustainability Reporting Practices: From A Developing Country Perspective? - Brishti Chakraborty (Universitas Trisakti, 2021)
This study examines the extent and nature of social, economic, and environmental reporting practices of Bangladeshi-listed banks. Using content analysis technique, Information was gathered from the available annual reports of 25 banks from 2014 to 2019. Findings revealed that overall reporting of environmental information has increased by 47% from 2014 to 2019, whereas overall social reporting has increased by 30% from 2014 to 2019. Again, we tried to explore sustainability reporting practices of these banks considering 26 categories too, where the first 12 categories are used to identify environmental accounting and reporting practices and the rest 14 for social and economic reporting. The findings of 26 categories of sustainability reporting reflect that social, economic, and environmental reporting has increased greatly by 74.90% in 2019. Most of the banks disclosed mostly about energy consumption (D6) from environmental reporting while economic social (D16), education, and training (D18), health and safety (D19) and culture (D20) from social perspectives and least about activities undertaken for tree plantation (D3) from an environmental perspective. This study has great implications for the policymakers of the corporate sector and government.